Evaluation of sorption isotherms in snacks with pregelatinized cassava - Cazzaniga, Amanda (2022)
Fil: Cazzaniga, Amanda. Universidad Nacional de Misiones. Facultad de Ciencias Exactas, Químicas y Naturales; Argentina.